Hubungan antara Dukungan Sosial Wali Kamar dengan Penyesuaian Diri Santri pada Tahun Pertama di SMPIT Pondok Pesantren Darul Fikri Sidoarjo: The Relationship between Dormitory Supervisors’ Social Support and The Students Self-Adjustment of in The First Year at Islamic Integrated Junior High School (SMPIT) Pondok Pesantren Darul Fikri Sidoarjo - Erinda Shofatil Himmah; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Student self-adjustment in Islamic boarding schools represents a critical developmental process, particularly during the first year of residence in a structured dormitory environment. Specific Background: At SMPIT Pondok Pesantren Darul Fikri Sidoarjo, first-year students face academic, social, and psychological demands requiring adaptive capacity supported by dormitory supervisors. Knowledge Gap: Limited empirical studies specifically examine the correlation between dormitory supervisors’ social support and self-adjustment among first-year junior high school students in Islamic boarding school settings. Aims: This study aims to analyze the relationship between dormitory supervisors’ social support and students’ self-adjustment. Results: Using a quantitative correlational design involving 94 first-year students and psychological scales measuring social support and self-adjustment, the findings reveal a significant positive correlation (r = 0.964; p < 0.001), with social support explaining 93% of the variance in self-adjustment. Social support includes emotional encouragement, appreciation, instrumental assistance, and informational guidance. Novelty: This study specifically highlights the central role of dormitory supervisors as daily social support providers within an Islamic integrated junior high school boarding context. Implications: The findings underscore the importance of strengthening dormitory-based support systems to facilitate adaptive processes among new students and suggest broader investigations across multiple boarding institutions to improve external validity. Keywords: Dormitory Supervisors, Social Support, Self-Adjustment, Islamic Boarding School, First-Year Students Key Findings Highlights: Social assistance from residential mentors accounts for 93% variance in adaptive capacity. Emotional, informational, appreciation, and practical guidance are strongly associated with students’ adaptation. Residential mentoring systems are central to psychological adjustment during the initial boarding year.